1991
DOI: 10.1002/jmv.1890350213
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of coronavirus‐mediated cell fusion by homeostatic control of cholesterol and fatty acid metabolism

Abstract: Cellular susceptibility to fusion mediated by murine coronavirus (mouse hepatitis virus, MHV strain A59) was separated into lipid-dependent and lipid-independent mechanisms with the use of subclones and selected mutants of mouse L-2 fibroblasts. Fusion-resistant L-2 cell mutants had similar cholesterol and fatty acid composition as did their fusion-susceptible parent subclone, and were presumably deficient in a genetically mutable non-lipid, host cell factor (e.g., fusion protein receptor). On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Studies with the N-terminal fusion peptide of HIV gp41 also suggest that cholesterol may play a role in HIV fusion (43,44), although these studies examine the fusion peptide out of the normal context of the intact virus envelope protein and its physiological fusion trigger of receptor and coreceptor (26). Studies of the coronavirus mouse hepatitis virus suggest that susceptibility to a lytic virus infection and generation of virus-induced syncytia may be influenced by cellular cholesterol content (11,16). Infection and fusion of African swine fever virus are affected by cellular cholesterol content (7), although the restricted host range of this virus of necessity required that these studies be performed in mammalian cells in which cholesterol depletion is limited and may produce toxic effects (26).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the N-terminal fusion peptide of HIV gp41 also suggest that cholesterol may play a role in HIV fusion (43,44), although these studies examine the fusion peptide out of the normal context of the intact virus envelope protein and its physiological fusion trigger of receptor and coreceptor (26). Studies of the coronavirus mouse hepatitis virus suggest that susceptibility to a lytic virus infection and generation of virus-induced syncytia may be influenced by cellular cholesterol content (11,16). Infection and fusion of African swine fever virus are affected by cellular cholesterol content (7), although the restricted host range of this virus of necessity required that these studies be performed in mammalian cells in which cholesterol depletion is limited and may produce toxic effects (26).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the SFV envelope itself is rich in SPM (Renkonen et al, 1971;Allan and Quinn, 1989). Furthermore, although it had been reported that the majority of the SPM would be located on the inner leaflet of the SFV bilayer (Van Meer et al, 1981), in a more recent study it was concluded that the SPM and PC in the SFV envelope are exposed at the outer surface (Allan and Quinn, 1989 (Malvoisin and Wild, 1990;Cervin and Anderson, 1991), including HIV (Sarin et al, 1985;Hansen et al, 1990;Aloia et al, 1988Aloia et al, , 1993. Like that of SFV, the envelope of HIV is rich in SPM and cholesterol (Aloia et al, 1988(Aloia et al, , 1993.…”
Section: Discussion Fusion Of Sfv Requires Sphingolipids In the Targementioning
confidence: 99%
“…Numerous studies have demonstrated that cell cultures exposed to M␤CD, a well-studied cyclic polysaccharide that specifically chelates cholesterol (39), become resistant to infection by a variety of enveloped viruses (7,49). That MHV infection might also be sensitive to M␤CD was suggested by the results of previous studies indicating that cholesterol-supplemented murine cells were hypersensitive to MHV-induced syncytia (13,19). Thus, we exposed murine 17 cl 1 fibroblast monolayers to increasing doses of M␤CD for 30 min at 37°C.…”
Section: Cholesterol Levels Can Determine Cellular Susceptibility To mentioning
confidence: 97%
“…Changes in the lipid composition of cellular membranes can have pronounced effects on the outcome of coronavirus infection. This was first documented in tissue culture, where the syncytia expanding from foci of murine hepatitis virus (MHV) infection were substantially larger after cholesterol supplementations (13,19,67). Subsequent in vivo experiments established correlations between cholesterol-rich diets and susceptibility of mice to pathogenic MHV infection (9).…”
mentioning
confidence: 98%